Comparison of Resistance, Aerobic and Combined Trainings Effects on the FGF21 Serum Levels in Active Elderly Men - Nory Nejad, Hassan; Abednatanzi, Hossein; Soheily, Shahram; Gholami, Mandana (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: The FGF-21 biomarker is an essential factor in reducing the incidence of various cancers and improving the metabolic status of individuals, and improving the metabolic of heart cells. This study aimed to assess the difference between the effect of resistance, aerobic, and combined training on the salivary levels of FGF-21 in active older men. Methods: The present study method was semi-experimental and performed with a pre-post-test design and three experimental groups. The subjects were randomly assigned to study 36 divided into three groups 1. Resistance training, 2. Aerobic training, and 3. Combined training (n = 12). The serum FGF-21 salivary value in subjects was evaluated and recorded using special sandwich analysis methods by special kits according to the kit brochure’s method. The subjects then performed relevant training protocols for eight weeks, after which the post-test data training was evaluated and recorded similar to the pretest conditions. Statistical analysis was performed using descriptive statistical tests, dependent t-test, one-way ANOVA, and Scheffe post hoc in SPSS version 24. The significant level was 0.05. Results: The results showed that the number of salivary FGF-21 increased significantly after applying aerobic, resistance, and combined training, and this increase was 38.9%, 23.8%, and 14.7% for combined, resistance, and aerobic activity, respectively. Conclusions: According to the findings of this study, combined exercises should be used to improve metabolic risk factors and reduce the risk of cancer due to increased FGF-21 levels in the elderly community.